Work–Life Balance and Psychological Well-Being among Generation Z Employees at PT X - Daniela Chrisel Amanda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to determine the relationship between work-life balance and psychological well-being among Generation Z employees at PT X. The background of this research stems from the phenomenon that many Gen Z employees experience low psychological well-being despite maintaining a relatively balanced work and personal life. This research employed a quantitative correlational method involving 120 Gen Z employees from the Quality Control (QC) division at PT X. Data were collected through online questionnaires using the Work-Life Balance Scale by Fisher et al. (2009) and Ryff’s Psychological Well-Being Scale (1989). The results of the Spearman’s rho correlation test revealed a significant negative relationship between work-life balance and psychological well-being (r = -0.322; p < 0.05). This indicates that a higher level of work-life balance is associated with lower psychological well-being, and vice versa. The findings suggest that achieving balance between work and personal life does not necessarily enhance psychological well-being without additional factors such as supportive work environments, social support, and opportunities for self-development. These results can serve as a reference for companies to design policies that promote the psychological well-being of Gen Z employees.